After the Empires - Preston, P. author. aut Link
XI, 272 p.
Keywords: The shift to the modern world in East Asia was accomplished in part via the experience of colonial rule in the late nineteenth century. Following imperial crisis in the 1930s and 1940s, independent nation states formed from which the political structure of East Asia is based today.